2016
DOI: 10.1017/s0305000915000562
|View full text |Cite
|
Sign up to set email alerts
|

Chinese L1 children's English L2 verb morphology over time: individual variation in long-term outcomes

Abstract: This study examined accuracy in production and grammaticality judgements of verb morphology by eighteen Chinese-speaking children learning English as a second language (L2) followed longitudinally from four to six years of exposure to English, and who began to learn English at age 4;2. Children's growth in accuracy with verb morphology reached a plateau by six years, where 11/18 children did not display native-speaker levels of accuracy for one or more morphemes. Variation in children's accuracy with verb morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 52 publications
5
67
2
Order By: Relevance
“…L1 Chinese children’s poor performance specifically in plural inflected forms, which is not shared by children speaking other L1s, reveals a specific problem with acquiring L2 inflections. This provides further support for the findings with older school aged children in Jia (2003), Jia and Fuse (2007), and Paradis et al (2016). Our results confirm that challenges in acquiring English inflections are not a general L2 learning phenomenon but is specific to Chinese-speaking children.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…L1 Chinese children’s poor performance specifically in plural inflected forms, which is not shared by children speaking other L1s, reveals a specific problem with acquiring L2 inflections. This provides further support for the findings with older school aged children in Jia (2003), Jia and Fuse (2007), and Paradis et al (2016). Our results confirm that challenges in acquiring English inflections are not a general L2 learning phenomenon but is specific to Chinese-speaking children.…”
Section: Discussionsupporting
confidence: 87%
“…Several recent studies of ECL2 learners report continued challenges in using inflectional morphology after many years of exposure to English. For example, Paradis et al (2016) found that Chinese-speaking children who began learning English at the age of 4 years continue to show difficulties with inflectional morphology after 6 years of English exposure. Some of the structures tested include tense inflections, e.g., past tense ‘ she cooked ,’ and third-person singular - s , e.g., “ she cooks now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See also Paradis et al (2016) for a description of long lasting delays in bilingual language development. If, however, such difficulties are taken as evidence for language impairment, overdiagnosis is particularly likely when monolingual norms are applied in tests of the majority language, which might be the weaker language for a child at the time of assessment.…”
Section: Introduction Bilingual Language Development and Language Impmentioning
confidence: 99%
“…Child-internal and child-external factors can influence language outcomes in comparable ways, as is illustrated by the partially overlapping language profiles of children with an inborn primary or specific language impairment (further on called LI) and children who are raised bilingually. Profound language delays have been documented for both children with LI (Rice, 2004; Krok and Leonard, 2015; Rice and Hoffman, 2015) and bilingual children (Bialystok et al, 2010; Farnia and Geva, 2011; Paradis et al, 2016), and comparisons of these two groups of children showed strikingly similar performance on core language domains, such as vocabulary and morphology (Grüter, 2005; Paradis, 2005; Blom and Boerma, 2017). It is, however, unknown whether these similarities are temporary and limited to certain developmental stages.…”
Section: Introductionmentioning
confidence: 99%